Acidity and Alcohol Levels of Goat’s Milk Yoghurt with the Addition of Black Rice Bran Flour During Cold Storage - Haskito, Ajeng Erika Prihastuti; Fatra, Ilhami Maulia; Mahdi, Chanif; Noviatri, Aldila; Adrenalin, Sruti Listra (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2024)
The development of yoghurt variations is increasingly diverse nowadays. The addition of black rice bran flour into yoghurt processing can increase the functional value of yoghurt, including increasing taste, antioxidant content, and dietary fiber. This research was to determine the effect of storage time in goat's milk yoghurt with the addition of black rice bran flour at a cold temperature of 4c on acidity and alcohol levels. The research used with 5 treatments, 4 repetitions. The treatment includes storage periods i.e., 0, 1, 2, 3 and 4 weeks. The acidity level will be calculated for each treatment group using the acid-base and alcohol titration method using the pycnometer method. The data obtained were analyzed using the one way ANOVA test followed by the Duncan Multiple Range Test. The results show that storage time has a very significant effect (p˂0.01) on acidity and alcohol levels. The highest acidity level was in week 2 (0.47%), then decreased continuously in weeks 3 and 4 of storage time. The alcohol content increased in line with storage time, reaching 0.0043% in week 4. If we look at the acidity and alcohol levels, the recommendation for consuming goat's milk yoghurt with the addition of black rice bran flour is no more than 1 weeks of storage time.